The Relationship Compensation Between and Job Insecurity with Turnover Intention for Employees at Hospital - Irmayani .; Rosita Ginting; Jul Asdar Samura; Luci Riani Ginting; Kurnia Alfiady; Anggi Isnani Parinduri (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2023)
The success and achievement of a company's goals is determined by the strategic role of its Human Resources (HR). Efforts are being made to achieve this, namely continuously optimizing the role of HR towards improving performance in supporting the sustainability of the organization/company. The hospital is a human resource-intensive organization due to the many professions involved in it. With many professions in the hospital, there are many problems that often arise which can ultimately hinder employee performance. One such problem is turnover. The purpose of this study is to explain the relationship between compensation and job insecurity with employee turnover intention at Grandmed Lubuk Pakam Hospital. Quantitative with a survey approach is the type of research used in this study. The research design used is cross-sectional. The population in this study were all employees at Grandmed Lubuk Pakam Hospital as many as 891 workers with a sample of 63 people who were taken using a purposive sampling technique. Data were analyzed using the chi square test with a significance level of 5% (CI=95%). The results showed that there is a relationship between compensation and turnover intention (p value = 0.006) and there is no relationship between job insecurity (p value = 0.184). It is hoped that decision makers in each agency will pay more attention to the needs of employees so that employees feel comfortable in carrying out their work.